Geography and regional development planning:linking understanding to action - Henk Huisman; Karmono Mangunsukardjo (Faculty of Geography, Universitas Gadjah Mada, 1986)
The interest in regional development planning in Indonesia as well as in many other Third World countries is growing rapidly since the early 1970s. However, the subject matter of regional development planning is still in the process of taking shape. As a consequence, considerable differences exist regarding the interpretation of this field of enquiry and action. The present article aims at addressing three basic questions, i.e.: (i) What is the rationale for the introduction of planning for development on a regional basis? (ii) What types of regional development planning do exist and what are their respective characteristics? and (iii) What are the various implications of the spatial dimension of regional development planning for professional practice? As the understanding of the dynamic situation in an area in a holistic way is a sine qua non condition for the planning of effective development intervention, the input of geography in the regional planning process is indispensable.